2008
DOI: 10.1136/thx.2007.086199
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation and gene expression in antioxidant related enzymes and risk of COPD: a systematic review

Abstract: Background: Observational epidemiological studies of dietary antioxidant intake, serum antioxidant concentration and lung outcomes suggest that lower levels of antioxidant defences are associated with decreased lung function. Another approach to understanding the role of oxidant/antioxidant imbalance in the risk of chronic obstructive pulmonary disease (COPD) is to investigate the role of genetic variation in antioxidant enzymes, and indeed family based studies suggest a heritable component to lung disease. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 78 publications
(123 reference statements)
1
54
0
3
Order By: Relevance
“…Acute loss of SOD3 in adult mice causes death, whereas low mortality rates are seen in SOD3-overexpressing animals exposed to hyperoxia, suggesting an essential role of SOD3 for survival (3,4). Accumulating evidence shows that SOD3 polymorphism is associated with a decline in lung function in rodents and humans, and susceptibility to COPD, which may be a result of alteration of its encoding protein structure, function, and level (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). However, it is unclear whether endogenous SOD3 participates in the development/ progression of the inflammatory response, leading to COPD/ emphysema.…”
mentioning
confidence: 99%
“…Acute loss of SOD3 in adult mice causes death, whereas low mortality rates are seen in SOD3-overexpressing animals exposed to hyperoxia, suggesting an essential role of SOD3 for survival (3,4). Accumulating evidence shows that SOD3 polymorphism is associated with a decline in lung function in rodents and humans, and susceptibility to COPD, which may be a result of alteration of its encoding protein structure, function, and level (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). However, it is unclear whether endogenous SOD3 participates in the development/ progression of the inflammatory response, leading to COPD/ emphysema.…”
mentioning
confidence: 99%
“…4B). Among oxidative stress-related genes, GCLC, GCLM, GPX5, GPX2, and G6PD have been implicated in GSH metabolism (23); therefore, we evaluated the intercellular reduced glutathione/oxidized glutathione (GSH/GSSG) ratio, one hallmark of oxidative stress (24). We found AGS and HT-29 cells suffered a marked GSH/GSSG imbalance following SW treatment for 0.5 and 24 hours (Fig.…”
Section: Sw Fraction Induces S Phase Arrest Apoptosis and Autophagymentioning
confidence: 98%
“…65 Gpx activity is significantly reduced in smokers and subjects with COPD, highlighting its prominent role in lung antioxidant defense. 63 With respect to reduced Gpx activity in COPD patients and smokers, erythrocyte Gpx activity was significantly lower in patients with severe COPD compared with patients with moderate COPD. 68 In addition, Gpx activity was decreased in plasma from COPD patients 69 and total blood from smokers and ex-smokers.…”
Section: Gpxs In Normal Physiology and Lung Diseasesmentioning
confidence: 99%
“…60 It has been shown that Gpx-2 is induced in the lungs of mice in response to cigarette smoke and that basal and CS-inducible expression of Gpx-2 are directly dependent on Nrf2. 61,62 In humans, Gpx-1 has been shown to be increased in COPD, 63 and Gpx-2 showed a three-to five-fold up-regulation in epithelial cells of smokers compared with nonsmokers. [64][65][66] Gpx-3 showed a two-fold up-regulation in epithelial cells of smokers compared with nonsmokers.…”
Section: Gpxs In Normal Physiology and Lung Diseasesmentioning
confidence: 99%